2016
DOI: 10.3389/fncir.2016.00066
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Orexin System on the Hypothalamus-Pituitary-Thyroid Axis

Abstract: Hypocretin/orexin (ORX) are two hypothalamic neuropeptides discovered in 1998. Since their discovery, they have been one of the most studied neuropeptide systems because of their projecting fields innervating various brain areas. The orexinergic system is tied to sleep-wakefulness cycle, and narcolepsy is a consequence of their system hypofunction. Orexinergic system is also involved in many other autonomic functions such as feeding, thermoregulation, cardiovascular and neuroendocrine regulation. The main aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 112 publications
(146 reference statements)
0
23
0
Order By: Relevance
“…Another important mediator related to obesity development is Orexin-A/Hypocretin 1, a neuropeptide synthesized in the lateral hypothalamus (Messina et al, 2016;Sperandeo et al, 2018). It plays an important role in the regulation of appetite: indeed, a reduction in the amount of Orexin-A determines a reduction of appetite (Inutsuka and Yamanaka, 2013;Messina et al, 2015;Chieffi et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Another important mediator related to obesity development is Orexin-A/Hypocretin 1, a neuropeptide synthesized in the lateral hypothalamus (Messina et al, 2016;Sperandeo et al, 2018). It plays an important role in the regulation of appetite: indeed, a reduction in the amount of Orexin-A determines a reduction of appetite (Inutsuka and Yamanaka, 2013;Messina et al, 2015;Chieffi et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma concentrations of triglyceride decreased significantly after the 1 st day of paradoxical SD but after 8 days of SD, the total cholesterol levels were not modified (10) .While, some studies reported a drop in both triglyceride and cholesterol levels in SD rats by lesions of VLPO nucleus (6) .On contrast, some studies reported higher triglyceride and cholesterol levels in rats subjected to SD (7) which may be due to dietetic factor. The drop in lipid concentration could be a result of high energy expenditure that contributes to energy deficit in sleep deprived rats (10) .This maybe explained by stimulation of stress hormones secretion specially thyroxine by orexin-B at the hypothalamic level (15) . conclusion SD leads to a rapid and remarkable drop in blood triglyceride levels with a slight and delayed drop in blood cholesterol level that can be explained by the high metabolic rate during periods of SD.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, these neurotransmitters alterations could explain also the sleep disorders such as nocturnal awakenings, insomnia, and parasomnias (Bramanti et al, 2012 ; Precenzano et al, 2017 ) and food selectivity in ASD children (Chistol et al, 2017 ; Li et al, 2017 ; Suarez, 2017 ). In this context may be explained the cerebral metabolism increasing (Mitelman et al, 2017 ) and the autonomic hyperfunctioning in ASD (Avola et al, 2004 ; Goodman, 2016 ; Parisi et al, 2017 ) sustained by high Orexin A levels (Messina et al, 2013 , 2014 , 2015 ; Kohyama, 2016 ; Messina A. et al, 2016 ; Messina G. et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%